2003
DOI: 10.1093/ndt/gfg435
|View full text |Cite
|
Sign up to set email alerts
|

High permeability haemofiltration improves peripheral blood mononuclear cell proliferation in septic patients with acute renal failure

Abstract: HP-HF restores PBMC proliferation in septic patients probably by eliminating immunomodulatory mediators. HP-HF may represent a new renal replacement therapy able to modulate PBMC function in sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 17 publications
0
41
0
1
Order By: Relevance
“…Others have studied membranes with higher cut off values (around 100 kDa). Their results show high SC and clearances, but albumin loss becomes significant (13,14,16,(21)(22)(23). With the membrane used in our study, albumin loss is timely and quantitatively limited (17,20).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Others have studied membranes with higher cut off values (around 100 kDa). Their results show high SC and clearances, but albumin loss becomes significant (13,14,16,(21)(22)(23). With the membrane used in our study, albumin loss is timely and quantitatively limited (17,20).…”
Section: Resultsmentioning
confidence: 60%
“…Moreover, De Vriese et al and Heering et al measured no IL-10, one of the most important anti-inflammatory cytokines (12), in ultrafiltrate during CWH with such membranes (7,8). A cut off membrane of 40 kDa means a SC of 0.05 or 0.1 for a 40 kDa molecule (13,14). These results are obtained in vitro and these cut offs could be decreased by up to 40% when they are calculated in vivo (15).…”
Section: Introductionmentioning
confidence: 91%
“…Previous studies showed the safe use of the Gambro HCO 1100 dialyzer in an intensive care setting (27,28). As predicted, we noted substantial albumin loss that required replacement on a regular basis (20 to 40 g per dialysis session and given as 20% human albumin solution).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, cytokine clearance rates were significantly higher in the HCO hemofiltration group. In another randomized study, HCO hemofiltration restored the monocyte proliferation capacity of septic patients, probably by eliminating immunomodulatory mediators [73]. However, the use of HCO hemofiltration has been challenged by the albumin loss, which can be up to 15 g per 4-hour session [74].…”
Section: High-adsorption Hemofiltration and High-cutoff Membranesmentioning
confidence: 99%